MHC class I assembly: out and about - Raghavan, Malini (2008)
The assembly of major histocompatibility complex (MHC) class I molecules with peptides is orchestrated by several assembly factors including the transporter associated with antigen processing (TAP) and tapasin, the endoplasmic reticulum (ER) oxido-reductases ERp57 and protein disulfide isomerase (PDI), the lectin chaperones calnexin and calreticulin, and the ER aminopeptidase (ERAAP). Typically, MHC class I molecules present endogenous antigens to cytotoxic T lymphocytes (CTLs). However, the initiation of CD8(+) T-cell responses against many pathogens and tumors also requires the presentation of exogenous antigens by MHC class I molecules. We discuss recent developments relating to interactions and mechanisms of function of the various assembly factors and pathways by which exogenous antigens access MHC class I molecules.